Cost-effectiveness of vedolizumab compared with conventional therapy for ulcerative colitis patients in the UK - Wilson MR; Azzabi Zouraq I; Chevrou-Severac H; Selby R; Kerrigan MC (Dove Medical Press, 2017)
Michele R Wilson,1 Ismail Azzabi Zouraq,2 Helene Chevrou-Severac,2 Ross Selby,3 Matthew C Kerrigan4 1RTI Health Solutions, Research Triangle Park, NC, USA; 2Takeda Pharmaceuticals International AG, Zurich, Switzerland; 3Takeda UK Ltd., Bucks, UK; 4PHMR Limited, London, UK Objective: To examine the clinical and economic impact of vedolizumab compared with conventional therapy in the treatment of moderately-to-severely active ulcerative colitis (UC) in the UK based on results of the GEMINI I trial. Methods: A decision-analytic model in Microsoft Excel was used to compare vedolizumab with conventional therapy (aminosalicylates, corticosteroids, immunomodulators) for the treatment of patients with UC in the UK. We considered the following three populations: the overall intent-to-treat population from the GEMINI I trial, patients naïve to anti-TNF therapy, and those who had failed anti-TNF-therapy. Population characteristics and efficacy data were obtained from the GEMINI I trial. Other inputs (eg, unit costs, probability of surgery, mortality) were obtained from published literature. Time horizon was a lifetime horizon, with costs and outcomes discounted by 3.5% per year. One-way and probabilistic sensitivity analyses were conducted to measure the impact of parameter uncertainty. Results: Vedolizumab had incremental cost-effectiveness ratios of £4,095/quality-adjusted life-year (QALY), £4,423/QALY, and £5,972/QALY compared with conventional therapy in the intent-to-treat, anti-TNF-naïve, and anti-TNF-failure populations, respectively. Patients on vedolizumab accrued more QALYs while incurring more costs than patients on conventional therapy. The sensitivity analyses showed that the results were most sensitive to induction response and transition probabilities for each treatment. Conclusion: The results suggest that vedolizumab results in more QALYs and may be a cost-effective treatment option compared with conventional therapy for both anti-TNF-naïve and anti-TNF-failure patients with moderately-to-severely active UC. Keywords: ulcerative colitis, cost-effectiveness, vedolizumab, inflammatory bowel disease